(untitled) (Texas Journal of Medical Science, 2022)
Treatment of fractures of the shin bones remains one of the most important problems not only in traumatology, but also in a number of related specialties. The duration of treatment of victims varies widely: from 3-4 months with closed tibial fractures without displacement to 5-7 months in cases of open injuries. With complicated fractures, they often reach 9-10 months or more. In the structure of disability, fractures of the lower leg occupy a leading place and account for 7.0–37.6% of all injuries of the musculoskeletal system.